The use of edible vertical greenery system to improve thermal performance in tropical climate / Hazril Sherney Basher … [et al.] - Basher, Hazril Sherney; Sheikh Ahmad, Sabarinah; Abdul Rahman, Abdul Malek; Qamaruz Zaman, Nurulhusna (Faculty of Mechanical Engineering and UiTM Press, 2016)
The vertical greenery system (VGS) is a passive shading and urban greening solution for multi-storey buildings. Buildings installed with VGS could benefit from lower indoor air temperature, which in turn will save energy. As cities are experiencing urban heat island due to excessive development and overpopulation, building occupants turn to mechanical cooling to cool the interior space. Normally, the VGS is installed with living aesthetic plants that function to absorb solar radiation. However, in this paper, Psophocarpus Tetrogonobulus (Winged Bean Plant) is selected as the plant medium based on its ability to provide vegetable pod, have longer lifespan and withstand heat gain from long sun exposure. This edible VGS could lower the building energy cooling load and at the same time provide food production at a household level. This paper presents a series of recently measured data from the use of Test Cell (ground level) at University Sains Malaysia, Penang. The VGS managed to reduce the surface temperature by an average of 2.4°C, while the maximum surface temperature drop achieved was 6.4°C. These promising results indicated that the VGS installed with edible plants such as wing beans could save energy through the benefits of shading in urban multi-storey buildings.